Identification and Characterization of a Novel Association between Dietary Potassium and Risk of Crohn’s Disease and Ulcerative Colitis - Khalili, Hamed; Malik, Sakshi; Ananthakrishnan, Ashwin N.; Garber, John J.; Higuchi, Leslie M.; Joshi, Amit; Peloquin, Joanna; Richter, James M.; Stewart, Kathleen O.; Curhan, Gary C.; Awasthi, Amit; Yajnik, Vijay; et al. (Frontiers in Immunology, 2016)
Background: Recent animal studies have identified that dietary salt intake may modify the risk and progression of autoimmune disorders through modulation of the IL23/TH17 pathway, which is critical in the pathogenesis of ulcerative colitis (UC) and Crohn’s disease (CD). Methods: We conducted a prospective study of U.S. women enrolled in the Nurses’ Health Study (NHS) and NHSII who provided detailed and validated information on diet and lifestyle beginning in 1984 in NHS and 1991 in NHSII. We confirmed incident cases of UC and CD reported through 2010 in NHS and 2011 in NHSII. We used Cox proportional hazards models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). In a case-control study nested within these cohorts, we evaluated the interaction between single nucleotide polymorphisms (SNPs) in genes involved in TH17 pathway and dietary potassium on risk of CD and UC. In a cohort of healthy volunteers, we also assessed the effect of supplemental potassium on development of naïve and memory T cells, differentiated with TGFβ1 or TH17 conditions. Results: Among a total of 194,711 women over a follow up of 3,220,247 person-years, we documented 273 cases of CD and 335 cases of UC. Dietary intake of potassium (Ptrend = 0.005) but not sodium (Ptrend = 0.44) was inversely associated with risk of CD. Although, both dietary potassium and sodium were not significantly associated with risk of UC, there was a suggestion of an inverse association with dietary potassium (Ptrend = 0.08). The association of potassium with risk of CD and UC appeared to be modified by loci involved in the TH17 pathway that have previously been associated with susceptibility to CD, particularly SNP rs7657746 (IL21) (Pinteraction = 0.004 and 0.01, respectively). In vitro, potassium enhanced the expression of Foxp3 in both naïve and memory CD4+ T cells via activating Smad2/3 and inhibiting Smad7 in TH17 cells. Conclusion: Dietary potassium is inversely associated with risk of CD with both in vitro and gene-environment interaction data suggesting a potential role for potassium in regulating immune tolerance through its effect on Tregs and TH17 pathway.